Is food promotion and marketing in the school food environment conducive to healthy choices for adolescents? Evidence from two West Africa countries - Bodjrenou Fifali, Sam Ulrich; Kossa, Yévèdo DG; Houndolo, Melina M.; Gnacadja, Djawou N; Hounkpatin, Waliou Amoussa; Jordan, Irmgard (2025)
Background: Food advertising is key component of food environment aiming to drive consumer demand for specific foods and dietary patterns. Objective: Analyse whether marketing aspects in the food environment of public elementary schools (PES) in Benin and Ivory Coast are conducive to healthy choices for adolescents.